Persepsi orang tua terhadap pendidikan Al-Qur’an anak di Desa Pondokagung - Adhawiyah, Robiatul (Maliki Interdisciplinary Journal, 2024)
The title of this study is “Parents’ Perception Toward Al-Quran Education of Children in Bocok District of Kasembon Regency”. The research question in this study is the parents’ perspective of al-Quran education of children in Bocok District. Therefore the purpose of this study are to analyze the background of parent choices toward al-Quran education and to describe the background of parents in Bocok district. The research approach that the researcher used in this research is the qualitative research approach with the data collection technique is question interviews. The respondents of this research are 4 parents with children who learn in Al-Quran education in Bocok district and the head minister of Quran education. The research result of this study are respondents agreed that Quran education is important for the future.